Attitudes Toward Four Levels of Self-Driving Technology Among Elderly Drivers - Lajunen, Timo; Sullman, Mark J. M. (Frontiers in Psychology, 2021)
Automatization and autonomous vehicles can drastically improve elderly drivers’ safety and mobility, with lower costs to the driver and the environment. While autonomous vehicle technology is developing rapidly, much less attention and resources have been devoted to understanding the acceptance, attitudes, and preferences of vehicle automatization among driver groups, such as the elderly. In this study, 236 elderly drivers (≥65 years) evaluated four vehicles representing SAE levels 2 to 5 in terms of safety, trustworthiness, enjoyment, reliability, comfort, ease of use, and attractiveness, as well as reporting preferences for vehicles employing each of the four levels of automation. The results of a repeated measures ANOVA showed that the elderly drivers rated the SAE level 2 vehicle highest and the fully automated vehicle (SAE 5) lowest across all attributes. The preference for the vehicle declined as a function of increasing automatization. The seven attributes formed an internally coherent "attitude to automatization" scale, a strong correlate of vehicle preference. Age or annual mileage were not related to attitudes or preferences for automated vehicles. The current study shows that elderly drivers’ attitudes towards automatization should be studied further and these results taken into account when developing automated vehicles. The full potential of automatization may not be realized if elderly drivers are ignored.